Comparative analysis of notified hand, foot, and mouth disease cases between Kelantan and Penang - Aziz, Aina Syazwani (2024)
Background: Hand Foot and Mouth Disease (HFMD), primarily caused by enteroviruses like EV 71 and CV-A16, remains a significant public health issue in Malaysia, particularly affecting children. Despite extensive efforts to manage HFMD, the incidence rate continues to rise, necessitating further investigation into regional differences and associated risk factors. Objectives: This study aims to estimate the incidence rates and risk factors of notified HFMD cases between the states of Kelantan and Penang from 2017 to 2021. Specifically, it seeks to identify differences in incidence rates and the distribution of cases by age, gender, and race. Methodology: A comparative cross-sectional study design was employed, utilizing secondary data from the Communicable Disease Control Information System (CDCIS) e-Notification. The study population included all notified HFMD cases in Kelantan and Penang from 2017 to 2021. Statistical analyses, including chi-square tests, were conducted using R software to estimate incidence rates and demographic factors between the two states. Results: From 2017 to 2021, 18,243 HFMD cases were reported, with 7,846 in Kelantan and 10,397 in Penang. The average incidence rate was higher in Penang (1.18 per 1,000 population) compared to Kelantan (0.49 per 1,000 population). The incidence was highest among children aged 0-4 years in both states, with significant differences in age distribution (χ2 (3) = 303.48, p < 0.05). Males had a higher prevalence of HFMD in both states, with a statistically significant difference in gender distribution (χ2 (1) = 6.885, p = 0.009). The Malay ethnic group had the highest number of cases in both states, but significant differences were observed in racial distribution (χ2 (4) = 4290.40, p < 0.05). Conclusion: The study reveals significant regional differences in HFMD incidence rates and demographic factors between Kelantan and Penang. The findings highlight the need for targeted public health interventions, particularly focusing on young children and incorporating comprehensive health education tailored to different ethnic groups. Enhanced surveillance systems are crucial for early detection and effective management of HFMD outbreaks.